BIOcity - Harrington, Anthony Joseph (2005)
This thesis seeks to offer strategies for the densification of various American cities developing its hypothesis through the use of biomimicry and the analysis of indigenous ecosystems. Solutions will be devised and tested based on methodologies of negotiation between man-made and natural systems and infrastructures. Metropolises to be studied will include New Orleans, Denver, Portland, New York and Phoenix. These cities were selected based on their locations within specific ecosystems (Wetlands, Prairie/Tundra, Evergreen, Broadleaf, Desert---respectively), their large populations, and expansive suburbs. Coherent research material on relevant issues will be presented (land use, population, pollution, transportation, etc.) and compared among the cities. Following, a comprehensive investigation of indigenous plants for each of these regions will be carried out, whereby strategies and hypothesis will be developed for interventions in each city/ecosystem variation. Physical planning strategies can be gleaned from these varying micro and macro ecosystems that have already existed, grown and adapted long before our cities were founded. Current localized systems of each city will be studied and alterations proposed to take advantage of unique indigenous conditions while allowing for farmland and natural area preservation, inclusion, and support of and within the system. (Abstract shortened by UMI.)